Theology in Melody: An Indigenous Theological Method of the Nepali Church - Bhandari, Pabitra Mani (Missiology, 2025)
Even after seven decades of Christianity in Nepal, an Indigenous Nepali theology has yet to emerge. Although Christianity is rapidly growing, it is unclear how the Nepali church is meeting its theological needs. Nepali Christians have long composed Christian hymns. This article argues that Nepali Christian leaders were unintentionally using songwriting to fulfill their duty of doing theology. This article focuses primarily on two tasks related to this topic. First, it argues that singing songs is a form of expression used by the Nepali people that the church may view as a theological method. Songs are the primary Indigenous tools available to people for developing social consciousness, speaking out against oppressive systems and discrimination, and creating a space to combat societal divisions. As a result, it is argued that songs could be used as a theological tool by the Nepali church. Second, this study looks at specific Christian songs to see how they are used in Nepali churches and what theological content they contain. It will show how Nepali Christians use music to express their love for their country and its people, as well as their desire to use the gospel to change society. This article also asserts that for Nepali Christians, Christian songs have served as a means of expressing, teaching, and learning about their faith, and thus have become their theology in melody. The argument is that the Nepali hymnal is unquestionably a theology book for Nepali Christians because it is available for every life event, including marriage, baptism, birth, and death, and directs their action in their context.